Make a Match Model Assisted With Flashcard in the Evaluation of History Learning - Maiyani, Ilen; Zulfa, Zulfa; Junaidi, Juliandry Kurniawan (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
This study aims to describe the design and implementation of the Make a Match learning model assisted by flashcards in the evaluation of history learning at SMAN 1 Sutera. The background of this study is the lack of interesting and effective learning methods in improving student activity and understanding. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the Make a Match model is implemented through three stages: introduction, core, and closing. Although this model succeeded in improving student activity and understanding, obstacles were found in the unevenness of student participation in group discussions. This study concludes that the Make a Match model is effective in creating an interactive learning atmosphere and improving understanding of the material, but improvements are needed in managing discussions for more optimal results.